Penyelesaian Sengketa Non-litigasi dalam Sejarah Peradaban Islam - Ririn Noviyanti (Institut Agama Islam Negeri (IAIN) Kediri, 2017)
Dispute settlements have two form, litigation and non-litigation. Some options as an alternative dispute resolution non-litigation include mediation, negotiation and arbitration. alternative dispute resolution has long been practiced in Islam to solve the problems. This qualitative-descriptive study uses a sociohistorical approach that examines and analyzes the practice of alternative dispute resolution in general, and mediation, negotiation, arbitration in particular. This study aims to discuss the theory of nonlitigation dispute resolution and its application in various areas of life in the classical Islamic era. The key issue explored in this research is how to implement non-litigation dispute resolution practices in Islamic history and the event that they are used. The conclusions of this study are; first, the practice of alternative dispute resolution has been done in the classical Islamic era on the event of retaking the Hajar Aswad by using the method of mediation. Second, the practice of negotiation on the event of the beginning of the Hudaibiyah treaty and the third, the practice of arbitration (tahkīm) on events involving Muawiyah and Ali bin Abi Talib in the battle of Shiffin.